Metabolizable energy of sorghum for laying japanese quails (Research, Society and Development, 2020)
In order to obtain greater profits in the production of laying Japanese quails, it is necessary to reduce the costs of formulating the diet, seeking to replace traditional foods with alternative ones. This work aims to evaluate the metabolizable energy values of low tannin sorghum for laying Japanese quails. There were two treatments and five repetitions, being treatment 1 with the reference diet based on corn and treatment 2 with 60% of the reference diet and 40% of low tannin grain sorghum. The quails were weighed, distributed, and received treatments according to a completely randomized design. The method of total collection was used to determine the apparent metabolizable energies (AME) and apparent corrected by the nitrogen balance (AMEn), with an adaptation period of four days and three days of excreta collection and measurement of feed intake. The values of AME were 3,124 kcal/kg and AMEn 3,075 kcal/kg, respectively.